Peran Komunikasi, Komitmen, dan Kompensasi dalam Meningkatkan Kepuasan Kerja Karyawan di Perusahaan XYZ: The Role of Communication, Commitment, and Compensation in Improving Employee Job Satisfaction at XYZ Company - Hariputra, Akbar; Sastryawanto, Hary; Siswati, Endang (Jurnal Ilmiah Manajemen Agribisnis, 2024)
This study aims to examine the effect of communication, commitment, and compensation on employee job satisfaction at XYZ company. Using quantitative methods and Structural Equation Modeling (SEM) analysis, this study involved 222 employees as samples. The results showed that communication and commitment have a significant effect on job satisfaction, both directly and through compensation mediation. Open communication and strong commitment from employees increase their job satisfaction, especially if supported by fair compensation. These findings reinforce the importance of internal factors in creating high job satisfaction, which ultimately has a positive impact on employee productivity and loyalty.